2017
DOI: 10.1073/pnas.1609711114
|View full text |Cite
|
Sign up to set email alerts
|

Changes in perceptual sensitivity related to spatial cues depends on subcortical activity

Abstract: Spatial cues allow animals to selectively attend to relevant visual stimuli while ignoring distracters. This process depends on a distributed neuronal network, and an important current challenge is to understand the functional contributions made by individual brain regions within this network and how these contributions interact. Recent findings point to a possible anatomical segregation, with cortical and subcortical brain regions contributing to different functional components of selective attention. Cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 37 publications
1
41
1
Order By: Relevance
“…When SC neuronal activity is perturbed by inactivation or microstimulation, performance in attention tasks is reliably altered in a spatially specific manner, even during covert tasks (Bogadhi et al, 2019;Bollimunta et al, 2018;Cavanaugh and Wurtz, 2004;Herman et al, 2018;Lovejoy and Krauzlis, 2010;Müller et al, 2005;Zénon and Krauzlis, 2012). During SC inactivation, improvements in perceptual sensitivity made possible by spatial cues are abolished (Lovejoy and Krauzlis, 2017). Despite SC inactivation preventing spatial cues from conferring a perceptual advantage, cue-related modulation of neuronal activity in extrastriate visual cortex remains robust during inactivation (Zénon and Krauzlis, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When SC neuronal activity is perturbed by inactivation or microstimulation, performance in attention tasks is reliably altered in a spatially specific manner, even during covert tasks (Bogadhi et al, 2019;Bollimunta et al, 2018;Cavanaugh and Wurtz, 2004;Herman et al, 2018;Lovejoy and Krauzlis, 2010;Müller et al, 2005;Zénon and Krauzlis, 2012). During SC inactivation, improvements in perceptual sensitivity made possible by spatial cues are abolished (Lovejoy and Krauzlis, 2017). Despite SC inactivation preventing spatial cues from conferring a perceptual advantage, cue-related modulation of neuronal activity in extrastriate visual cortex remains robust during inactivation (Zénon and Krauzlis, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in a previous study using the same paradigm, the authors showed that neurons' firing rates in visual area V4 are modulated by shifts in d', but not in c (Luo and Maunsell, 2015). These results can be considered in conjunction with two recent studies in the superior colliculus (SC) (Lovejoy and Krauzlis, 2017;Sridharan et al, 2017). They found that SC contributes to attention through changes in both d' and c, with the latter being the dominant contribution.…”
mentioning
confidence: 64%
“…Recent studies from other laboratories support the idea that different brain structures have distinct relationships to behavioral changes in criterion and sensitivity (69,70). These reports focused on the SC, and, together, they indicate that neurons in the SC contribute to behavioral changes in either criterion or sensitivity, but with criterion being the more prominent component.…”
Section: T I M Ementioning
confidence: 85%